The challenges of global occurrence of aflatoxin M1 contamination and the reduction of aflatoxin M1 in milk over the past decade. (November 2020) - Min, Li; Li, Dagang; Tong, Xiong; Sun, Hao; Chen, Weidong; Wang, Gang; Zheng, Nan; Wang, Jiaqi
Abstract: The incidence of aflatoxin M1 (AFM1) contamination in milk and milk products is a serious health hazard for human worldwide. Thus, the global monitoring of AFM1 in raw milk has been ongoing for decades. In this review, the occurrence of AFM1 in raw milk has been summarized worldwide in 32 countries date from 97 references over the past decade. The data from 28 references demonstrated that a great risk related to high AFM1 concentrations (above 500 ng/L) in raw milk exist in several countries. Furthermore, to minimize health risks associated with ubiquitous exposure to AFM1 contamination in milk, several detoxification methods have been tested to lessen the transfer of aflatoxins from feed (7.3–112 μg/kg) to milk (190–1920 ng/L). Although most of them could lessen the concentrations of AFM1 in milk (76–1840 ng/L), these methods are still substandard relative to the EU limit (50 ng/L). The limitation of detoxification approaches in milk might suggest that comprehensive solutions should be implemented containing the standardization of legitimately harvest, storage, and lifetime of feedstuff, the application of detoxification methods, the establishment of official monitoring and regulatory limits, and so on.